Unconventional pharmacology of a neuronal nicotinic receptor mutated in the channel domain. - Bertrand, D (1992)
The putative channel-forming MII domains of the nicotinic, gamma-aminobutyric acid type A, and glycine receptors contain a highly conserved leucine residue. Mutation of this hydrophobic amino acid in the neuronal nicotinic receptor alpha 7 (Leu-247), reconstituted in Xenopus oocytes, modifies the ionic response to acetylcholine and alters desensitization. Furthermore, the Leu----Thr (L247T) mutant has two conducting states (46 pS and 80 pS), in contrast with the wild-type (WT) receptor, which has only one (45 pS). We now show that this mutant possesses a rather paradoxical pharmacology: antagonists of the WT receptor such as dihydro-beta-erythroidin, hexamethonium, or (+)-tubocurarine elicit ionic currents when applied to the L247T alpha 7 mutant and these responses are blocked by alpha-bungarotoxin. Furthermore, prolonged application of acetylcholine causes desensitization in the WT but leads to a potentiation of the responses to acetylcholine or dihydro-beta-erythroidin in the mutant. These data are consistent with a scheme in which mutation of Leu-247 renders a desensitized state in the WT channel a conducting state. They also strengthen the proposal that, in the WT, some competitive antagonists may stabilize desensitized states. Finally, these observations may shed light on properties of other ion channels, in particular the glutamate receptors, which display multiple conductance levels associated with various pharmacological agents.